2017
DOI: 10.1007/s00405-017-4453-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and preferences of patients visiting a head and neck oncology outpatient clinic: a qualitative study

Abstract: The objective of this study is to report on an in-depth evaluation of patient experiences and preferences at a Head and Neck Oncology outpatient clinic. A qualitative research design was used to determine the experiences and preferences of Head and Neck Cancer patients in an Oncology Outpatient Clinic, Maastricht University Medical Center, The Netherlands. Head and Neck Cancer Patients, treated for at least 6 months at the Oncology Clinic, were included. A qualitative research design with patient interviews wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 28 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…It should be stressed that there were far more similarities than differences in preferences and needs between the BCC and SCC patient groups. In addition, qualitative studies with patients with melanoma and even patients with other types of cancers have demonstrated many similar themes, for example the need for more information and lack of trust in their GP . Whereas some needs and preferences may be relevant to all types of patients (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that there were far more similarities than differences in preferences and needs between the BCC and SCC patient groups. In addition, qualitative studies with patients with melanoma and even patients with other types of cancers have demonstrated many similar themes, for example the need for more information and lack of trust in their GP . Whereas some needs and preferences may be relevant to all types of patients (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The search summary flowchart following PRISMA guidelines is presented in figure 1. The search yielded 12,446 references following deduplication, and 18 studies/n=19 papers [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] were retained and synthesised in this review. The characteristics of included studies are summarised in box 1.…”
Section: Resultsmentioning
confidence: 99%
“…All retained studies (n=18/18) reported data from high-income, Western countries. ► The Netherlands (n=5/18) [36][37][38][39][40] ► Canada (n=3/18) [41][42][43] ► Australia (n=3/18) 44 45 49 ► USA (n=2/18) 46 50 ► UK (n=1/18) 47 ► Ireland (n=1/18) 53 ► Norway (n=1/18) 48 ► Sweden (n=1/18) 54 ► Germany (n=1/18 study reported in n=2/18 papers) 51 52 Healthcare settings ► Hospital wards (n=5/18) 37 38 41 47 48 ► Residential aged care facilities (n=3/18) 44 45 54 ► Outpatient clinics (n=2/18) 36…”
Section: Countries and Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another parameter reflecting quality of care is how patients experience its delivery. It is important to know the needs and preferences of patients and assess their perceptions and experiences [87,88]. There are several methods to measure these preferences and experiences including interviews and the use of patient-reported experience (PRE) questionnaires.…”
Section: Patient Experiencesmentioning
confidence: 99%